2019
DOI: 10.1111/cod.13373
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy to hair cosmetic allergens in Thailand

Abstract: Background: Hair cosmetics such as hair dyes, bleaching, waving, and cleansing products are composed of numerous chemical ingredients. Allergic reactions to these contact allergens, other than p-phenylenediamine, are rarely reported.Objectives: To study the incidence of patch test reactions to hair cosmetic allergens and identify the factors associated with hair cosmetic allergy in Thailand. Methods:We retrospectively reviewed the case records of patients who underwent patch testing from 2009 to 2018. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 29 publications
(65 reference statements)
4
17
1
2
Order By: Relevance
“…In agreement with our results, hairdressers with ACD have been previously reported to be mainly female, affected at a relatively young age at the beginning of their careers 13‐16 . On the other hand, hair dye consumers are sensitized at a relatively older age, because most customers use hair dyes to conceal their grey hair and hair greying usually starts in the third or fourth decade of life 9,10 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with our results, hairdressers with ACD have been previously reported to be mainly female, affected at a relatively young age at the beginning of their careers 13‐16 . On the other hand, hair dye consumers are sensitized at a relatively older age, because most customers use hair dyes to conceal their grey hair and hair greying usually starts in the third or fourth decade of life 9,10 …”
Section: Discussionsupporting
confidence: 90%
“…Hair dyes include a variety of chemical agents with sensitizing potential for both customers and hairdressers. PPD is the major component of oxidative hair dyes and the contact allergen of prime concern 1,8‐10 . Patch testing is the standard method for investigating sensitization and contact allergy to hair dyes.…”
Section: Introductionmentioning
confidence: 99%
“…As to the p-phenylenediamine sensitization prevalence, children may be exposed to the chemical via henna tattoos and black rubber toys; adults are more likely to encounter it through hair dyes, resulting in their higher sensitization prevalence. 28 In the case of ACD to cosmetic-related allergens, it needs to be noted that children could be potentially sensitized not only from their own personal products but also from the products used by their parents. 29,30 Careful history-taking and inspecting the list of ingredients on patients' products is required.…”
Section: Discussionmentioning
confidence: 99%
“…Additional analysis of the product information in our Contact Allergens Avoidance Program database revealed that only 5 of 218 (2.3%) baby products contained lanolin, which was much less than that reported in other countries. As to the p ‐phenylenediamine sensitization prevalence, children may be exposed to the chemical via henna tattoos and black rubber toys; adults are more likely to encounter it through hair dyes, resulting in their higher sensitization prevalence 28 . In the case of ACD to cosmetic‐related allergens, it needs to be noted that children could be potentially sensitized not only from their own personal products but also from the products used by their parents 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…A Thai study assessed 2842 patients patch tested to allergens commonly found in HCPs and found that 23.3% (n = 663) had positive reactions; however, clinical relevance and source exposure were not documented. 4 Here, we characterize positive patch test allergens and document ICD associated with HCPs.…”
mentioning
confidence: 99%